Pengalaman Adaptasi Budaya Pekerja Perempuan Indonesia di Australia dalam Lingkungan Kerja Multikultural - Tyas Rahmatika; Nusaibah Dzakiyah Mujahidah; Rafa Islami Nabila; Nadea Laras Wati; Raditya Dega Mahaputra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Globalization has increased cross-border labor mobility, including Indonesian female workers working in Australia. Differences in work culture and social environment become major challenges in the adaptation process. This study aims to analyze the cultural adaptation experiences of Indonesian female workers in Australia within a multicultural work environment using the U-Curve theory approach. This research uses a descriptive qualitative method through semi-structured interviews with one informant who has worked in Australia for 1.4 years in a meat packing factory. The data were analyzed using a thematic descriptive approach based on the U-Curve stages. The results show that the informant experienced stages of cultural adaptation including honeymoon, culture shock, adjustment, and mastery. The main challenges include differences in communication style, individualistic attitudes, and work pressure. However, through openness and mental resilience, the informant was able to adapt successfully.